Plan de mejoramiento para la empresa Montallantas Ltda en la ciudad de Armenia. (2014)
The present improving plan performed in Motollantas Company is focused to the continuing improving of the organization, proposing a better use of the internal processes of the company, in this way we could offer a better service and attention to our customers. Analyzing the principal failures of the organizational and the strategic addressing, principally it is focus in the researching in the motorcycle market in Armenia this is in PLAN DE MEJORAMIENTO MOTOLLANTAS order to supplying the necessities of the motorcycle riders in the city. The company does not account with a variety of services such as technical services, and selling accessories for the motorcycles. Investigations and strategies are formulated in order to the company increases its sales in approximately 50% in that way it gives a market recognition because this is a clue fact in that way the company could get more profitability in its company‟s activities and also it guarantees a better improvement in its organizational system and in its strategic addressing.